A novel ETFDH mutation in an adult patient with late-onset riboflavin-responsive multiple acyl-CoA dehydrogenase deficiency. (4th March 2018) - Chen, Min; Peng, Jing; Wei, Wei; Wang, Rui; Xu, Hongliang; Liu, Hongbo
ABSTRACT: Aim of the study: To report a novel mutation in the electron transfer flavoprotein dehydrogenase (ETFDH) gene in an adult patient with late-onset riboflavin-responsive multiple acyl-CoA dehydrogenase deficiency. Materials and methods: The genomic DNAs from a patient whose main clinical presentations are muscles weakness and hypoglycemia was analysed. Results: The patient was identified to carry compound heterozygous mutations in ETFDH gene. Two missense mutations c.814 G > A and c.389 A > T were found. Conclusion: This is the first report of c.814G > A mutation in ETFDH in adult patient with MADD.